Appling The Co – Integration Method approach by autoregressive distributed lag model ARDL) To Estimate the Factors Affecting the Rate of Sudanese Economic Growth (1990- 2020) - Ahmed, Imtithal Mergny Mohammed; Abdelateef, Afra Hashim (Journal of Economic, Administrative and Legal Sciences, 2022)
This study aims to analyzing and measuring the relationship between exports, imports and remittances of Sudanese working abroad on the rate of economic growth in Sudan during the period (1990- 2020) using the co –integration approach by autoregressive distributed lag model (ARDL) to estimate the relationship in the long and short term between the variables of the study. The results show that there is a long – term equilibrium relationship between the variables of the study and that exports and imports have a positive impact on the rate of economic growth in the long and short terms.it also found remittances of Sudanese working abroad have a negative impact on the rate of economic growth in the long and short terms, and this is due to the fact that most of these remittances are transferred to the country in an informal way.